2015
DOI: 10.1517/17425247.2015.1021678
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in the delivery of epigenetic drugs

Abstract: Introduction Advancements in epigenetic treatments are not only coming from new drugs but from modifications or encapsulation of the existing drugs into different formulations leading to greater stability and enhanced delivery to the target site. The epigenome is highly regulated and complex; therefore it is important that off-target effects of epigenetic drugs be minimized. The step from in vitro to in vivo treatment of these drugs often requires development of a method of effective delivery for clinical tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 109 publications
0
19
0
Order By: Relevance
“…Moreover, besides being an attractive strategy to control HOXA9 expression at the epigenetic level, it is worth noting that most, if not all, of the epigenetic drivers presented here have an effect on the expression of many other genes. Consequently, such approaches that change the epigenetic marks may not exclusively be active on the leukemic cells of AML patients, but may also present side-effects and off-target effects by altering normal cells [299,300,301,302]. Moreover, such epigenetic targeting would not be restricted to HOXA9 but be also active on other members of the posterior HOXA locus, namely HOXA5 to HOXA11, which are usually epigenetically co-expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, besides being an attractive strategy to control HOXA9 expression at the epigenetic level, it is worth noting that most, if not all, of the epigenetic drivers presented here have an effect on the expression of many other genes. Consequently, such approaches that change the epigenetic marks may not exclusively be active on the leukemic cells of AML patients, but may also present side-effects and off-target effects by altering normal cells [299,300,301,302]. Moreover, such epigenetic targeting would not be restricted to HOXA9 but be also active on other members of the posterior HOXA locus, namely HOXA5 to HOXA11, which are usually epigenetically co-expressed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lipid nanocarriers can protect a drug from acidic degradation, increase intestinal permeability, and promote oral absorption, for example, there is promising evidence to support the use of a nanostructured lipid carrier for the oral delivery of decitabine [121]. Another medium, nanogels (NGs), can be designed to release their encapsulated drug in response to the patient’s physiological environment or specific conditions such as temperature, pH, or molecular recognition [122]. Decitabine-loaded NG has been used to circumvent drug resistance mechanisms in cancer cell lines [123] (Fig.…”
Section: Epigenetic Approaches In Nanomedicinementioning
confidence: 99%
“…However, epidrugs are unstable in vivo and has transient antiproliferative effect [138, 139]. To safely and effectively deliver epidrugs, nanocarriers have been employed to extend dosing regimen and improve PK profiles.…”
Section: Examples Of Nanocarrier-based Combination Therapies Of Camentioning
confidence: 99%